APP IMPERIALISM: THE POLITICAL ECONOMY OF THE CANADIAN APP STORE - Nieborg, David; Young, Chris; Joseph, Daniel (AoIR Selected Papers of Internet Research, 2018)
In this paper, we introduce the notion of app imperialism by exploring the political economy of the Canadian iOS App Store. Building on Dal Yong Jin’s concept of "platform imperialism", we argue that US companies dominate global app stores through the systematic acquisition of capital resources. App imperialism marks the outsized economic footprint and influence of US companies in national app stores. Using a longitudinal financial dataset, we qualitatively coded the top-50 of revenue-generating game apps in April 2015 and 2016. Distinguishing between value creation (generating revenue) and value capture (appropriating profit) allowed us to determine the plight of Canadian app developers. While the Canadian App Store exhibits a large degree of source diversity, featuring a high number of active app developers, we found the ability of Canadian developers to both create and capture value negligible. US owned developers, publishers, parent-organizations, and intellectual properties, on the other hand, were overrepresented. These initial findings suggest that any potential growth in the Canadian app economy will be increasingly captured by US-owned companies. These results question the effectiveness of Canadian cultural policy frameworks, which have been particularly proactive in supporting Canada-based game studios. While our initial analysis offers just a temporal and regional snapshot of the App Store’s political economy, it gestures towards broader critical material issues related to platform capitalism and app diversity.